2020
DOI: 10.17648/acta.scientiae.5315
|View full text |Cite
|
Sign up to set email alerts
|

Lesson Study in Initial Teacher Education to Stimulate the Pedagogical Content Knowledge on the topic of Speed of Sound

Abstract: The lesson study is a collaborative model of teacher professional development originating in Japan, which has received growing international attention. This multifaceted model can be considered from many points of view. This research aims to understand what physics and chemistry pre-service teachers learn, in the domain of the pedagogical content knowledge on the speed of sound, in a lesson study. Participants were all pre-service teachers (three) attending the first year of their initial teaching education pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Aproximadamente el 45 % de las publicaciones están relacionadas con los procesos de formación docente. Con ella se promueven programas de desarrollo profesional para los profesores de ciencias en cuanto a generar aspectos de mejora de la práctica pedagógica, como en las intervenciones de desarrollo profesional docente como Lesson Study (Coenders & Verhoef, 2019;Conceição et al, 2020Conceição et al, , 2021. Esta se refiere a los procesos de formación que desarrollan grupos de docentes que se reúnen de forma regular para trabajar en el diseño, desarrollo, comprobación, crítica o mejora de una lección (Soto-Gómez et al, 2021).…”
Section: Formación Docenteunclassified
“…Aproximadamente el 45 % de las publicaciones están relacionadas con los procesos de formación docente. Con ella se promueven programas de desarrollo profesional para los profesores de ciencias en cuanto a generar aspectos de mejora de la práctica pedagógica, como en las intervenciones de desarrollo profesional docente como Lesson Study (Coenders & Verhoef, 2019;Conceição et al, 2020Conceição et al, , 2021. Esta se refiere a los procesos de formación que desarrollan grupos de docentes que se reúnen de forma regular para trabajar en el diseño, desarrollo, comprobación, crítica o mejora de una lección (Soto-Gómez et al, 2021).…”
Section: Formación Docenteunclassified
“…Research on lesson studies as a teacher professional development process has shown promising results (e.g., Conceição et al, 2016;Juhler, 2018;Sims & Walsh, 2009;Zhou, Xu, & Martinovic, 2016), but investigations with Science teachers are still scarce, mainly involving inquiry tasks in Physics teaching. Moreover, much research on lesson studies involves initial teacher education in Mathematics (e.g., Baptista et al, 2014;Ponte, Quaresma, Mata-Pereira, & Baptista, 2016) and few in Physics (e.g., Baptista et al, 2013;Conceição, Baptista, & Ponte, 2020;Conceição et al, 2019;Pektas, 2014;Rodrigues & Arroio, 2020).…”
Section: Lesson Study Cyclementioning
confidence: 99%
“…Lesson Studies are herald as contributing to teachers professional development but also to teachers' professional knowledge [2]. This holds true to the ones involved in each study but also to others that have access to the refined lesson plans and records of students' reactions, difficulties, and results.…”
Section: Lesson Studiesmentioning
confidence: 99%